Numerical methods for engineers : with programming and software applications - Chapra, Steven C.; Canale, Raymond P. (Boston : WCB/McGraw-Hill, 1998)
Mathematical modeling and engineering problem-solving. Computers and software. Approximations and round-off errors. Truncation errors and the taylor series. Bracketing methods. Open methods. Roots of polynomials...
Includes index.
Keywords: Data processing; Engineering mathematics; Numerical calculations; Microcomputers -- Programming; Numerical analysis -- Data processing; Engineering mathematics -- Data processing